Why Nationalism - Tamir, Yael, 1954- (Princeton University Press, 2020)
The surprising case for liberal nationalismAround the world today, nationalism is back--and it's often deeply troubling. Populist politicians exploit nationalism for authoritarian, chauvinistic, racist, and xenophobic purposes, reinforcing the view that it is fundamentally reactionary and antidemocratic. But Yael (Yuli) Tamir makes a passionate argument for a very different kind of nationalism--one that revives its participatory, creative, and egalitarian virtues, answers many of the problems caused by neoliberalism and hyperglobalism, and is essential to democracy at its best. In Why Nationalism, she explains why it is more important than ever for the Left to recognize these positive qualities of nationalism, to reclaim it from right-wing extremists, and to redirect its power to progressive ends. Provocative and hopeful, Why Nationalism is a timely and essential rethinking of a defining feature of our politics.